1996
DOI: 10.1212/wnl.47.3.813
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of MRI lumbosacral nerve root enhancement in acute Guillain-Barre syndrome

Abstract: Nerve root enhancement of the cauda equina occurs in Guillain-Barré syndrome (GBS), but the frequency, diagnostic value, and meaning of this finding is unknown. We prospectively obtained gadolinium-enhanced lumbosacral spine MRIs in 24 consecutive patients with acute GBS and blindly rated nerve root enhancement as absent, mild, or prominent. The MRIs were obtained 13 days, mean, after onset of symptoms (range 2 to 42 days). Twenty of 24 patients had cauda equina nerve root enhancement, which was mild in 6 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(76 citation statements)
references
References 8 publications
4
70
0
2
Order By: Relevance
“…Neurosarcoidosis, chronic meningitis, Guillain-Barre syndrome, and many infectious cases of meningitides can cause the linear leptomeningeal enhancement seen on MRI. 49 Bacterial and viral meningeal inflammation tends to appear as linear enhancement, whereas fungal inflammation is generally nodular. 50 Primary nerve sheath tumors in the subarachnoid space may also appear as areas of nodular enhancement.…”
Section: Imaging In Differential Diagnosismentioning
confidence: 99%
“…Neurosarcoidosis, chronic meningitis, Guillain-Barre syndrome, and many infectious cases of meningitides can cause the linear leptomeningeal enhancement seen on MRI. 49 Bacterial and viral meningeal inflammation tends to appear as linear enhancement, whereas fungal inflammation is generally nodular. 50 Primary nerve sheath tumors in the subarachnoid space may also appear as areas of nodular enhancement.…”
Section: Imaging In Differential Diagnosismentioning
confidence: 99%
“…[12][13][14][15][16] Although prominent nerve root enhancement has been observed along with an increased severity of leg weakness, 14 the correlation between intracranial findings and clinical outcomes is poorly established. 13,17,18 It was previously suggested that enhancement solely of the anterior CE roots was indicative of GBS, but it is now known that both the anterior and posterior roots may be simultaneously involved.…”
Section: Involvement Of the Ce Rootsmentioning
confidence: 99%
“…In fact, one of the initial historical cases of the acute motor sensory variant of GBS was found, on review, to be a case of paralytic rabies [87]. Participation of autoantibodies against peripheral nerve antigens in the evolution of paralysis is also suggested by vivid enhancement of ventral and dorsal nerve roots on magnetic resonance imaging, similar to GBS [77,88]. However, neither neutralizing antibodies nor antiganglioside nor myelin basic protein antibodies have been consistently demonstrated in CSF in paralytic rabies [78,81,89].…”
Section: Bat Rabiesmentioning
confidence: 99%